La influencia de la familia en el rendimiento escolar de los niños/as de la escuela de educación básica IV Centenario n° 2 Loja - Ortega Jaramillo, Karina Patricia (2016)
"The view from a holistic perspective is a family group consisting of subsystems that its members would yet integrated into a system that is society." The family is modified, persists as a stable structure that adapts to the social environment; when considered as a system implies that it is unity and integrity, so we can not reduce to the sum of the characteristics of its members. Poor school performance is indeed a problem of alarming dimensions, many have been concerned to find its causes, to explain different approaches, to discover the factors that give rise to this problem. Improving performance means not only get high marks for the students, but to increase the degree of psychological satisfaction, welfare of students themselves. In the family bond, the School of Basic Education "IV Centenario No.2 Loja" are children who are part of a team of several people who joined together form a system family business, the family is the core of all society where values are learned, practice respect and that is where the good life is encouraged. To carry out this investigation arose how main objective: "Improve Educational Achievement of children parallel 6th Year Basic Education" A "School for Basic Education IV Centenario No.2 Section Loja Evening". 5 For the field research, the method was used Community Self-Development through the stages as Stage One: Initial exchange with the subject in need of professional action. Second Stage: Pre Formulation - Diagnosis. Stage Three: The process itself of Diagnostics and Solutions; breach of the research methodology, because this only allows you to reach the formulation of a pre - diagnosis. And the use of statistical method for the analysis and interpretation of results which are presented in tables and graphs below. The results of this research are summarized in the following: Underperforming School, School is notorious because children are not in a proper emotional state, being a cause attributed to this problem; Families at the School are dysfunctional because the relationship of parents to children is not adequate ie family if affects school performance of children, having as causes emotional instability causing poor performance in them.